2015
DOI: 10.4103/1673-5374.150711
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of icariin contributes to peripheral nerve regeneration and functional recovery

Abstract: Our previous study showed that systemic administration of the traditional Chinese medicine Epimedium extract promotes peripheral nerve regeneration. Here, we sought to explore the therapeutic effects of local administration of icariin, a major component of Epimedium extract, on peripheral nerve regeneration. A poly(lactic-co-glycolic acid) biological conduit sleeve was used to bridge a 5 mm right sciatic nerve defect in rats, and physiological saline, nerve growth factor, icariin suspension, or nerve growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Despite the reports that ICA stimulates the proliferation and differentiation of the stem cells in vitro [ 13 , 14 ], little is known on the effect of ICA on neural stem cells proliferation. In the present study, we prepared neural stem cells from rat hippocampus, and confirmed the properties of the proliferation and differentiation of the neural stem cells, and demonstrated that ICA significantly augments the growth and proliferation of the primary neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the reports that ICA stimulates the proliferation and differentiation of the stem cells in vitro [ 13 , 14 ], little is known on the effect of ICA on neural stem cells proliferation. In the present study, we prepared neural stem cells from rat hippocampus, and confirmed the properties of the proliferation and differentiation of the neural stem cells, and demonstrated that ICA significantly augments the growth and proliferation of the primary neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ICA stimulates the proliferation and differentiation of human bone mesenchymal stem cells promoting bone formation [ 11 , 12 ]. Recent studies demonstrated that local administration of icariin inhibits neuron apoptosis and promote the regeneration of peripheral nerve and functional recovery [ 13 , 14 ]. However, whether ICA can regenerate neuronal cells and improve the function of neurodegenerative disorders through potentiating the proliferation and differentiation of neural stem cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Since ALP (an early marker of osteogenic differentiation) levels peak on the 14 th day of the in vitro BMSC culture with ICA [121, 126, 135], it is reasonable to consider 14 days of intravenous ICA administration for the treatment regimen. ICA also promotes the regeneration of periodontal tissue [137], peripheral nerves [138], neural stem cells [139], and endometrium [140], although the optimal concentration of ICA differs across tissues.…”
Section: Prospectsmentioning
confidence: 99%
“…Peripheral nerve injury occurs in ~2.8% of trauma patients (3) and various methods have previously been used to repair this in a clinical setting (46). However, the most effective approach for the regeneration of nerve defects remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral nerve injury is typically caused by accidents, contusion, compression, tumour resection or congenital deformities and may result in total or partial loss of motor, sensory and autonomic functions ( 1 , 2 ). Peripheral nerve injury occurs in ~2.8% of trauma patients ( 3 ) and various methods have previously been used to repair this in a clinical setting ( 4 6 ). However, the most effective approach for the regeneration of nerve defects remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%